Marketing communication model at baitul maal wal tamwil integrated joint enterprises Sidogiri Melaya Bali, Indonesia - Siswanto, Adil (Journal of Commerce, Management, and Tourism Studies, 2025)
The primary aim of the research paper are (1) The integrated marketing communication model increase the number of customers at the Baitul Maal Wal Tamwil Integrated Joint Enterprises Sidogiri Melaya Bali branch office, (2) The challenges of implementing the integrated marketing communication model to customers, (3) Face the challenges of implementing an integrated marketing model to customers at branch office Malaya Bali. This research approach uses a descriptive qualitative approach. Qualitative approach, with data collection techniques by observation, interviews and documentation. Practical Applications (1) The integrated marketing communication model can ensure that the messages conveyed by various communication channels, such as advertising, direct marketing and social media, are social and mutually supportive, thereby increasing consumer awareness and trust in brands and products. (2) Challenges from demographics and psychographics among consumers can cause messages that are ineffective or irrelevant, so many customers may not understand the principles of sharia finance and its benefits. Effective and inclusive education needs to be prepared to explain concepts such as profit sharing, usury free, and fairness in transactions. (3) Choose the right communication channel based on your goals and target audience. An integrated marketing communications model can ensure that messages conveyed by various communication channels, such as advertising, direct marketing and social media, are social and mutually supportive, thereby increasing consumer awareness and trust in brands and products.